Comparison of the Hepatic Effects of Phenobarbital in Chimeric Mice Containing Either Rat or Human Hepatocytes With Humanized Constitutive Androstane Receptor and Pregnane X Receptor Mice. (31st July 2020) - Yamada, Tomoya; Ohara, Ayako; Ozawa, Naoya; Maeda, Keiko; Kondo, Miwa; Okuda, Yu; Abe, Jun; Cohen, Samuel M; Lake, Brian G
Abstract: Using a chimeric mouse humanized liver model, we provided evidence that human hepatocytes are refractory to the mitogenic effects of rodent constitutive androstane receptor (CAR) activators. To evaluate the functional reliability of this model, the present study examined mitogenic responses to phenobarbital (PB) in chimeric mice transplanted with rat hepatocytes, because rats are responsive to CAR activators. Treatment with 1000 ppm PB for 7 days significantly increased replicative DNA synthesis (RDS) in rat hepatocytes of the chimeric mice, demonstrating that the transplanted hepatocyte model is functionally reliable for cell proliferation analysis. Treatment of humanized CAR and pregnane X receptor (PXR) mice (hCAR/hPXR mice) with 1000 ppm PB for 7 days significantly increased hepatocyte RDS together with increases in several mitogenic genes. Global gene expression analysis was performed with liver samples from this and from previous studies focusing on PB-induced Wnt/β-catenin signaling and showed that altered genes in hCAR/hPXR mice clustered most closely with liver tumor samples from a diethylnitrosamine/PB initiation/promotion study than with wild-type mice. However, different gene clusters were observed for chimeric mice with human hepatocytes for Wnt/β-catenin signaling when compared with those of hCAR/hPXR mice, wild-type mice, and liver tumor samples. The results of this study demonstrate clear differences in the effects of PB on hepatocyte RDS and global gene expression between human hepatocytes of chimeric mice and hCAR/hPXR mice, suggesting that the chimeric mouse model is relevant to humans for studies on the hepatic effects of rodent CAR activators whereas the hCAR/hPXR mouse is not.